Developing The Financial-Banking System to Accelerate the Transition to A Green Economy - Carmen Cornelia PULBERE-GHELASE; Mihaela NECULITA; Daniela Ancuta SARPE (Communications of International Proceedings, 2024)
At the macro level, the companies need financial instruments, whose policy promotes the social dimension and the slow growth of their desirable business models. In order to support the transition of the financial system, the standards related to the financial market, which will be implemented in the sustainability reports of the participants of the financial markets, offer increased protection to investors, through the lens of the obligation to inform about the approach to sustainability from the producers of financial services and also from the sellers of financial products. The regulations that support the transition to a more sustainable economy of the financial system involves the sustainability of financial products. The real contribution to the transition to the green economy is supported by the correct and valuable information published by users regarding how to approach and how to reduce any negative effect of investments on society, as a whole and on the environment. The methodology of the paper consists of documentary research, direct research, studies conducted by the NBR, EBA, Eurostat, CNSM, ECB, data analysis and interpretation (graphs, tables, diagrams), experience of over 20 years in banking The aim of the research is to identify the best ways to improve and to accelerate the development of the financial-banking market, an important pillar in the transition to an economy with zero carbon emissions.
Keywords: banking sustainability; green economy; sustainable development